The Effect of Workload and Job Stress on Nurse Burnout in Kuningan Regency: An Integrated JD-R and Transactional Theory Perspective - Angga Wisnu Tio Octora; Dharliana Hardjowikarto; Juwita Juwita (Institut Agama Islam Sunan Giri Ponorogo, 2026)
to increasing job demands and psychological pressures. This study aims to examine the effects of workload and job stress on nurse burnout in Kuningan Regency through an integrated Job Demands–Resources (JD-R) and Transactional Theory perspective. A quantitative associative approach was employed, involving 106 nurses as respondents. Data were collected using structured questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that both workload and job stress have significant positive effects on nurse burnout, with workload emerging as the more dominant predictor. Collectively, these variables explain a substantial proportion of burnout, highlighting the important role of both job demands and psychological stress in shaping nurses' well-being. The results suggest that burnout develops not from a single factor but from the interaction between excessive work demands and prolonged psychological strain. This study contributes theoretically by strengthening the integration of JD-R Theory and the Transactional Theory of Stress and Coping in explaining burnout among nurses. Empirically, it provides a more comprehensive understanding of burnout through the simultaneous examination of workload and job stress. Practically, the findings emphasize the need for healthcare institutions to implement integrated workload management and stress reduction strategies to improve nurse well-being and healthcare service quality.